An exploratory study of prevailing knowledge, attitude and practice of husband in regards to factors affecting in supporting activities during pregnancy, delivery and post-partum periods - Bhatta, Bimala (Journal of Nobel Medical College, 2012)
Background: The study aimed to study knowledge, attitude and practice of husband and factors affecting in supporting activities during pregnancy, delivery and postpartum period at Khairahani VDC of Chitwan district. The general objective of the study was to identify husband’s involvement in making safe pregnancy, delivery and postpartum period. Methods: A cross sectional, descriptive and non-experimental study design was conducted using quantitative methods. Sampling method was purposive and study population was father of fewer than one year age group children. Data was collected using structured questionnaire by interview method. Results: Majority of husbands had low knowledge about support during pregnancy, delivery and postpartum period while activities did for support was very negligible regardless of knowledge. Most of the husbands don’t know about danger signs during pregnancy. Very low level of knowledge was found about birth preparedness, emergency obstetric conditions during delivery period. Husbands took decision regarding place of delivery in majority. Half of the respondent’s don’t know about complications during postpartum period. Education level was found to be non-supporting factor for knowledge of support during pregnancy. Education of husband increased the knowledge of birth preparedness during pregnancy. Family size has influence the support during postpartum period. There was no association between income of husband and support provided during delivery. Conclusion: The knowledge level of support was found to be low during pregnancy, delivery & postpartum period along with supporting activities. Similarly there was low knowledge of emergency obstetric condition; danger signs during pregnancy and post-partum period. The practice of birth preparedness was found to be unsatisfactory regardless of knowledge. DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7287 Journal of Nobel Medical College Vol.1(1) 2011 45-52